Literature Review: Potential of Chinese Ketepeng Leaves (Cassia alata L.) as an Antibacterial Agent - Apriliana, Rizky Ayu; Hasbi, Nurmi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Infectious diseases are diseases caused by bacteria. Several bacterial infectious diseases include bacteria that cause skin infections such as Staphylococcus aureus, Staphylococcus epidermidis, Propionibacterium acnes and Streptococcus pyogene, nosocomial pneumonia infections of the urinary tract by Pseudomonas aeruginosa and Klebsiella pneumoniae that cause Healthcare-Acquired Infections (HAIs). The drugs usually used to treat bacterial infections are antibiotics. Along with the increase in cases of infection, there is also an increase in the use of antibiotics. Widespread or irrational use of antibiotics can cause resistance, so alternatives are needed to overcome them. One plant that has potential as an antibacterial agent is the leaves of Chinese Ketepeng (Cassia alata L.). Chinese ketepeng leaves contain phytochemical compounds, namely flavonoids, saponins, tannins, alkaloids and phenols. Therefore, this literature review aims to determine the potential of Chinese Ketepeng (Cassia alata L.) leaf extract as an antibacterial agent. The method used is the Systematic Literature Review method by collecting data through databases such as Publish or Perish, PubMed, and Google Scholar. The search method uses the keywords